Implementasi Algoritma K-Nearest Neighbor Dalam Mendiagnosis Kurap Pada Kucing - Marsono Marsono; Asyahri Hadi Nasyuha; Saiful Nur Arif; Muhammad Zunaidi; Nur Yanti Lumban Gaol (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Ringworm is an infectious disease caused by keratinophilic fungi on the surface of the skin or other parts of tissues that contain keratin (fur, nails, hair, and horns) in animals and humans. Some fungal species are zoonotic because infected animals can be a source of transmission to humans and vice versa. This disease is often found in domesticated animals and is the oldest mycotic disease in the world. This skin disease is called ringworm because it is thought to be caused by worms and because the symptoms begin with inflammation of the skin's surface which if left unchecked will enlarge to form a ring like circle. The K-Nearest Neighbor (KNN) algorithm is a method for classifying new objects. KNN is a supervised learning algorithm, where the results of new query instances are classified according to the majority of categories in KKN. The class that appears the most is the class resulting from the classification. Nearest Neighbor is an approach to calculate the proximity between the new case and the old case, which is based on matching the weights of a number of existing features. This study aims to make it easier for patients to know the health condition of their pet cat.